SATURATION FLOW OF A RIGHT-TURN LANE AT ONE SIGNALISED INTERSECTION IN BANDUNG - BAHRI (NIM 25098086); Pembimbing: Ir. Titi Liliani Soedirjo, M.Sc. dan Ir. Willy Tumewu, M.Sc, SAMSUL
In signalized intersection capacity analysis, Indonesian Highway Capacity Manual (MKJI) 1997, calculated the saturation flow rate in every observed approach by determining the Passenger Car Equivalents (PCE) to the opposed approach (type 0) or protected approach (type P). Webster (1966) said that for unopposed right-turning with exclusive right-turn lane, the saturation flow rate calculation should be obtained separately by using considered PCE. The saturation flow rate is also influenced by radius of curvature. The purpose of this study is to derive the saturation flow rate in a right-turn lane and the saturation flow rate in lane of straight-ahead in unopposed condition on a signalized intersection. The location of the study is on Jl. Buah Batu-JI. Soekarno Hatta, which has an isolated fixed time traffic signal. The data of cycle time and the saturated traffic flow were collected by video camera at peak hours in the morning and the afternoon on a workday in May 2000. By using PCE of unopposed movement (MKJI, 1997), the result shows that the saturation flow rate in a right-turn lane is 1806 pcu/hour and the rate in lane of straight ahead is 2175 pcu/hour. The saturation flow rate in lane of straight ahead is 20% over the rate in lane of right-turning. At 95 percent confidence level, by using Z-test, these values for lane widths of 3.5m., are significantly different. Meanwhile, the observation on cycles which contain only light vehicles, shows that right-turning saturation flow rate is 1800 pcu/hour and straight-ahead saturation flow rate is 2271 pcu/hour. The results of PCE calculation show that in a right-turn lane the value of Passenger Car Equivalent of light vehicle (PCELV) is 1.0 , Passenger Car Equivalent of heavy vehicle (PCEHV) is 1.2, Passenger Car Equivalent of motor cycle (PCEMC) is 0.3, and in the lane of straight-ahead the value of PCELV is 1.0 , PCEHV is 1.3, and PCEMc is 0.2. The correction factor of light vehicles on the right-turn lane is 1,3 times one on the straight-ahead lane.